Validity of a New Kit Measuring Salivary Lactate Dehydrogenase Level for Screening Gingivitis. (26th February 2017) - Ekuni, Daisuke; Yamane-Takeuchi, Mayu; Kataoka, Kota; Yokoi, Aya; Taniguchi-Tabata, Ayano; Mizuno, Hirofumi; Miyai, Hisataka; Uchida, Yoko; Fukuhara, Daiki; Sugiura, Yoshio; Tomofuji, Takaaki; Morita, Manabu
Abstract : Aim . The aim of this study was to determine the usefulness of a new kit that can evaluate salivary lactate dehydrogenase (LD) level in real time for screening gingivitis. Materials and Methods . The study included 70 systemic healthy volunteers [29 males and 41 females; mean age ± SD: 24.1 ± 2.6 years]. Resting saliva was collected from each participant and LD level was evaluated in real time using the kit (a color-changing sheet with an integer scale ranging from 1 to 10). A dentist measured probing pocket depth, clinical attachment level, and the proportion of sites with bleeding on probing (% BOP) at six sites on all teeth. Gingivitis was diagnosed when the BOP value was ≥20%. Results . Salivary LD level was positively correlated with mean % BOP (odds ratio: 1.47, 95% confidence interval: 1.132–1.916, and P < 0.001 ) in a logistic regression model. The sensitivity and specificity of the kit were 0.89 and 0.98, respectively, at a cut-off value of 8.0 for LD level. Conclusions . The new kit for measurement of salivary LD level may be a useful tool to screen for gingivitis in young adults, which contributes to early detection of future periodontitis.